Patient Attitudes and Beliefs and Provider Practices Regarding Antibiotic Use for Acute Respiratory Tract Infections in Minya, Egypt - Amr Kandeel; Waleed El-Shoubary; Lauri A. Hicks; Mohamed Abdel Fattah; Kathleen L. Dooling; Anna Leena Lohiniva; Omnia Ragab; Ramy Galal; Maha Talaat (MDPI AG, 2014)
The inappropriate use of antibiotics in the community is one of the major causes of antimicrobial resistance. This study aimed to explore the physician prescribing pattern of antibiotics for acute respiratory infections (ARIs) and to explore the knowledge, attitudes, and practices of patients regarding antibiotic use for ARIs. The study was conducted in Upper Egypt and used quantitative and qualitative research techniques. Eligible patients exiting outpatient clinics with ARIs were invited to participate in the study. A qualitative study was conducted through 20 focus group discussions. Out of 350 encounters for patients with various ARIs, 292 (83%) had been prescribed at least one antibiotic. Factors significantly associated with antibiotic prescribing for adults included patient preference that an antibiotic be prescribed. For children younger than 18, presentation with fever, cough, loss of appetite, and sore throat, along with the caregiver's antibiotic preference, were associated with an antibiotic prescription. Several misconceptions regarding antibiotic use among community members were stated, such as the strong belief of the curing and prophylactic power of antibiotics for the common cold. Interventions to promote proper antibiotic use for ARIs need to be piloted, targeting both physicians and the public. Educational programs for physicians and campaigns to raise public awareness regarding proper antibiotic use for ARIs need to be developed.